Effect of Polyaniline/Graphene Oxide Thickness as A Gas Sensor Material for Robusta Coffee Aroma Tests - Mulyono, Tri; Asnawati, Asnawati; Wulandari, Silvia Sri (JKPK (Jurnal Kimia dan Pendidikan Kimia), 2023)
The intricate aroma of coffee arises from a complex blend of volatile compounds, each characterized by distinct attributes and intensities. This study focuses on synthesizing and characterizing the PANI/GO composite. It explores the impact of sensor thickness, rooted in the PaNi/GO composite, on its responsiveness to coffee aroma. Moreover, the findings hold promise as a reference point for sensor development. The PANI/GO composite, doped with HCl, was synthesized using a chemical oxidative polymerization technique in an aqueous solution, employing ammonium persulfate (APS) as the oxidant. Functional group analysis was conducted on the synthesized PANI/GO composite via FTIR (Fourier Transform Infrared). Subsequently, the composite was employed to create a gas sensor with varying thicknesses—0.14, 0.21, 0.28, 0.35, and 0.44 mm. This PANI/GO gas sensor was evaluated using robusta coffee steam from the Sidomulyo region, with resistance measurements performed using a multimeter. The optimization process encompassed sensor conductivity, sensitivity, response time, and repeatability considerations. The most effective sensor thickness emerged as 'Sensor 4,' possessing a 0.35 mm thickness, showcasing a conductivity of 4.69 x 10-9 S/cm, sensitivity of 0.67, response time of 18 seconds, and repeatability of 2.10%. These outcomes hold significant implications for enhancing sensor design and performance, particularly in capturing intricate aromatic profiles such as coffee scents.